Learning from IDA Experience : Lessons from IEG Evaluations, with a Focus on IDA Special Themes and Development Effectiveness - Independent Evaluation Group (World Bank, Washington, DC, 2019)
The 18th replenishment of the International Development Association (IDA18), one of the world’s major providers of financial resources to the poorest countries, was the largest in the institution’s 56‐year history. Together with significant changes in its policy and financing framework, IDA’s enhanced commitment authority was expected to enable faster progress toward the international community’s far‐reaching and ambitious 2030 agenda,1 which aligns closely with the World Bank Group’s twin goals of eradicating extreme poverty and boosting shared prosperity in a sustainable manner. The objective of this synthesis report is to draw on findings and lessons from recent IEG evaluations (that is, those completed since FY16) and databases that are pertinent to IDA18 special themes and IDA support more generally to inform forthcoming IDA19 discussions. The synthesis report focuses on learning from IDA experience over the last 10 years in relation to areas covered by the IDA18 special themes, drawing on relevant IEG evaluations completed since FY16.